Technology review. Python and automated laboratory system control. - Cahn MH; Russo MF (JALA: Journal of the Association for Laboratory Automation, 2007)
The Python programming language is reviewed, with an emphasis on features and add-on modules useful for solving problems in the field of laboratory automation. Complexities of multi-instrument automated system control and coordination are discussed, along with the difficulties that arise when multitasking is used to implement system controllers. We introduce Python's generators, a feature not found in other popular languages, and demonstrate how to use them to simplify the development of multi-instrument laboratory automation system controllers.